Analisis Kemampuan Pemahaman Konsep Siswa pada Materi Hidrokarbon Menggunakan Three-Tier Multiple Choice Diagnostic Instrument : Literature Review - Marsya Divya Olii; Nurhayati Bialangi; Julhim S. Tangio; Mangara Sihaloho; Erga Kurniawati (Jurnal Pendidikan Kimia, Fisika dan Biologi, 2025)
This study aims to analyze students’ conceptual understanding of hydrocarbons through a literature review utilizing the Three-Tier Multiple Choice Diagnostic Instrument. Hydrocarbons are a fundamental topic in chemistry education that often leads to student misconceptions. The three-tier diagnostic instrument is designed not only to assess students’ cognitive knowledge through correct or incorrect answers but also to explore the reasoning behind their choices, enabling more accurate identification of misconceptions and conceptual understanding. The methodology employed is a literature review examining various scientific sources on the application of this diagnostic tool in teaching hydrocarbon concepts. The findings indicate that the Three-Tier Multiple Choice Diagnostic Instrument is effective in systematically detecting and classifying students’ difficulties and misconceptions. Furthermore, the use of this instrument contributes significantly to developing targeted and data-driven instructional strategies to enhance students’ conceptual mastery in chemistry. The implications of this study highlight the necessity of integrating three-tier diagnostic instruments in the assessment process to support optimal learning outcomes in hydrocarbon material.